PENGELOLAAN MANAJEMEN KEUANGAN BAGI UMKM DI DESA JOHO KECAMATAN MOJOLABAN KABUPATEN SUKOHARJO - Erni Widiastuti; Sarsiti (FAKULTAS EKONOMI UNIVERSITAS SURAKARTA, 2023)
Abstract The objective of implementing the counseling program for the management of Joho Village, Mojolaban District, Sukoharjo Regency is to provide discourse to business actors on the importance of understanding financial management for UMKM in Joho Village, Mojolaban District, Sukoharjo Regency. The activity method is carried out using two methods: (a) Presentation (the material presented in community service activities is about how business actors are able to manage financial management properly and how business actors are able to compile financial reports in the form of powerpoint) (b) Questions and answers and discussion the result of the implementation of the extension program is that actors in Joho Village who are members of UMKM are able to understand the meaning of financial management well, business actors are able to manage finances well, and business actors can prepare simple financial reports. Keywords: counseling, management of financial management, UMKM